Unpredictable stability: the governor’s case in the Belarusian-Lithuanian Region under Paul I in 1796–1801 - Lukashevich, Andrei M. (Journal of the Belarusian State University. History, 2022)
The article presents a generalised portrait of civil governors of the Belarusian-Lithuanian Region under Paul I in 1796–1801. The social characteristics (origin, religion, age, educational level, career, awards) of eight Lithuanian, Belarusian and Minsk civil governors are analysed. The conditions and motives for the appointment and dismissal of these officials are established. It is noted that the governor corps of the Belarusian-Lithuanian Region under Paul I was characterised by both all-Russian tendencies (frequent turnover, a higher rank according to the Table of Ranks, the absence of a clearly established amount of pensions), and some features (regional and confessional affiliation, elderly age (50 years on average)). It is concluded that in the personnel policy, Paul I continued Catherine’s practice of appointing former military governors, which was explained both by political (disloyalty of part of the population) and ethno-confessional (Jews, Catholics, Uniates, Orthodox) features of the region. The daily life of governors is reconstructed on the basis of socio-cultural characteristics (number of duties, perception of time, personal qualities, material support, marital status and interests). It is concluded that the origin, patronage and military experience played an important role in the appointment. However, the duration of tenure under Paul I depended on the business qualities of the governors. It is noted that some bosses, having no managerial experience, made numerous mistakes. They led to dissatisfaction with the emperor and, as a result, to premature resignations. At the same time, the reign of Paul I turned out to be quite effective in the Belarusian-Lithuanian Region in terms of achieving managerial results.
Keywords: civil governor; Belarusian province; Lithuanian province; Minsk province; Ya. I. Bulgakov; I. G. Frizel; Z. Ya. Karneev; G. M. Osipov; S. S. Zhegulin; M. S. Belokopytov; P. I. Severin; P. M. Tarbeev